Respiratory Medicine at McMaster University, Hamilton, Ontario: 1968 To 2013 - Norman L Jones; Paul M O’Byrne (Canadian Respiratory Journal)
The medical school at McMaster University (Hamilton, Ontario) was conceived in 1965 and admitted the first class in 1969. John Evans became the founding Dean and he invited Moran Campbell to be the first Chairman of the Department of Medicine. Moran Campbell, already a world figure in respiratory medicine and physiology, arrived at McMaster in September 1968, and he invited Norman Jones to be Coordinator of the Respiratory Programme.